NILAI PENDIDIKAN KARAKTER DALAM MITOS PULAU SENUA - Suhardi Suhardi (Jurnal Bahasa Lingua Scientia, 2020)
The people of Natuna Regency are very rich in various forms of myth. One of them is the myth of Senua Island. The purpose of this research is to describe the values of character education contained within the myth of Senua Island. Data collection techniques are performed using document engineering. While data analysis is conducted using data analysis techniques submitted by Miles and Hubberman in Moleong 2007, i.e. (1) carrying out a short story, (2) performing data reduction, (3) presenting the data, (4) interpret the data obtained in accordance with the theory, and (5) to compile the sympulsion. Results of the research obtained is the myth of Senua Island contains the value of character education, such as: value (a) aspect of the Keislaman, (b) tolerance, (c) "honesty, (d) hard work, (e) creative, (f) Mandiri, (g) The National Spirit, (h) friendly/communicative, (i) The love of peace, and the value of (j) responsibility.